Fostering Children's Independence: Behavioral Modification Strategies for Diaper Dependency - Putu Riana Artyanti Putri; Putu Ayu Onik Pratidina; Ratna Devy Winayanti; Dita Lestari; Fiqih Amalia (Psikostudia : Jurnal Psikologi, 2025)
Children who were accustomed to using diapers often experienced difficulties in breaking this habit, requiring effective intervention strategies to enhance independence in using the toilet. This study aimed to evaluate the effectiveness of the modeling method in improving toilet training skills in children through video-based intervention and positive reinforcement. The research method used was an experimental approach with a Single-Subject Experimental Design (SSED) utilizing an A-B-A-B reversal design to observe behavioral changes before and after the intervention. The results indicated that the client was able to understand instructions and imitate toilet training behaviors from the provided video, showing an increase in the frequency and duration of not using diapers at home. However, the client still faced difficulties in defecating in the toilet and continued to use diapers in certain situations, such as at school or during sleep. The implications of this study suggested that the modeling method could be an effective strategy in establishing toilet training habits with consistent environmental support and appropriate reinforcement, making it applicable in broader educational and parenting contexts. Anak yang terbiasa menggunakan pampers sering mengalami kesulitan dalam melepas kebiasaan tersebut sehingga diperlukan strategi intervensi yang efektif untuk meningkatkan kemandirian dalam menggunakan toilet. Penelitian ini bertujuan untuk mengevaluasi efektivitas metode modeling dalam meningkatkan keterampilan toilet training pada anak melalui intervensi berbasis video dan reinforcement positif. Metode penelitian yang digunakan adalah eksperimen dengan desain Single-Subject Experimental Design (SSED) menggunakan A-B-A-B reversal design untuk mengamati perubahan perilaku sebelum dan sesudah intervensi. Hasil penelitian menunjukkan bahwa klien mampu memahami instruksi dan meniru perilaku toilet training dari video yang diberikan serta mengalami peningkatan dalam frekuensi dan durasi tidak menggunakan pampers di rumah. Namun, klien masih mengalami kesulitan dalam buang air besar di kloset dan tetap menggunakan pampers dalam situasi tertentu seperti saat berada di sekolah atau tidur. Implikasi dari penelitian ini menunjukkan bahwa metode modeling dapat menjadi strategi efektif dalam membentuk kebiasaan toilet training dengan dukungan lingkungan yang konsisten serta reinforcement yang tepat sehingga dapat diterapkan secara lebih luas dalam konteks pendidikan dan pengasuhan anak.